Participation in breast cancer screening among breast cancer survivors –A nationwide register-based cohort study. (December 2020) - Larsen, Mette Bach; Vejborg, Ilse; Njor, Sisse Helle
Abstract: The aim of this study was to analyse if breast cancer survivors without other breast imaging surveillance attend population-based screening differently than women not previously diagnosed with breast cancer. Further, to analyse if any differences depended on the women's age and years since previous cancer diagnosis. The study was a register-based retrospective cohort study of all women invited to participate in the national breast cancer screening programme in 2015–2016. Participation rates were calculated for breast cancer survivors without breast imaging within 21 months (2–4 years, 4–6 years, 6–10 years and more than 10 years after diagnosis) and for women without previous breast cancer. Relative differences in participation rates between the two groups were calculated. A total of 679, 990 women were included in the study (2.6% breast cancer survivors). For breast cancer survivors, participation rates increased with increasing number of years since the previous cancer diagnosis peaking at 80.3% if the cancer diagnosis was more than 10 years ago. For women with no previous breast cancer, participation rate was 80.3%. The relative difference in participation was highest close to the breast cancer diagnosis and for the youngest women participation rates remained lower among breast cancer survivors even more than 10 years after the diagnosis. In conclusion, regardless of age and years since previous breast cancer diagnosis, breast cancer survivors had lower or similar participation rates than women with no previous cancer diagnosis. This indicated that as many as one fifth of the breast cancer survivors are at risk of inadequate surveillance. Highlights: Breast cancer surveillance needs to be optimised owing to the amount of survivors. No evidence contradicts surveillance could be within organised screening programmes. One fifth of survivors do not participate entailing a risk of suboptimal surveillance. Surveillance in organised screening requires attention to the special needs of survivors.